Non-intubated Thoracoscopic Surgery to Minimize Contamination From Airway Secretions During the COVID-19 Pandemic - Wang, Man-Ling; Hung, Ming-Hui; Hsu, Hsao-Hsun; Cheng, Ya-Jung; Chen, Jin-Shing (Frontiers in Surgery, 2022)
Background: General anesthesia and tracheal intubation potentially pose a high risk to health care workers (HCWs) managing surgical patients during the coronavirus disease 2019 (COVID-19) pandemic. Nonintubated anesthesia is a rational way of managing patients undergoing thoracoscopic surgery that avoids tracheal intubation and minimizes the aerosols generated during airway instrumentation. The purpose of this study was to determine whether nonintubated anesthesia in combination with a face mask is safe and feasible in patients undergoing thoracoscopic surgery. Methods: A total of 18 patients who underwent nonintubated thoracoscopic surgery with a face mask during the perioperative period between March 9, 2020 and April 6, 2020 were included. The main outcomes were anesthetic management and postoperative results. Results: The 18 patients had a mean age of 64 years and a body mass index of 22.9 kg/m2. All patients wore a mask during induction of anesthesia and throughout surgery. Three patients underwent lobectomy, four segmentectomy, ten wedge resection, and one underwent anterior mediastinal tumor resection. No patient developed cough or vomiting during the perioperative period. All patients were transferred to the postoperative recovery unit within 15 minutes of the end of surgery (average 7.2 min). No patient required conversion to tracheal intubation or conversion to thoracotomy. Conclusion: Nonintubated anesthesia with a mask was safe and feasible in patients undergoing thoracoscopic surgery. Avoidance of intubated general anesthesia and use of a lung separation device may reduce the risk to HCWs of contamination by airway secretions, thereby conserving personal protective equipment, especially during the COVID-19 pandemic.